Lupus nephropathy and vasculitis. (October 2019) - Willcocks, Lisa; Egan, Allyson; Jones, Rachel
Abstract: Multisystem autoimmune diseases, including systemic lupus erythematosus (SLE) and vasculitis, are inflammatory conditions of unknown cause. Renal involvement can occur in a variety of forms and usually represents a severe disease manifestation. SLE is complicated by renal involvement (lupus nephritis) in over one-third of patients. Small vessel vasculitides, including antineutrophil cytoplasmic antibody-associated and antiglomerular basement membrane disease, also frequently affect the kidneys, causing a rapidly progressive glomerulonephritis. Histologically, this manifests as a necrotizing, crescentic glomerulonephritis. This is potentially reversible, but if left untreated generally results in end-stage renal failure and death within days to weeks. A crescentic glomerulonephritis can also be seen in SLE, but this is not the typical pattern of lupus nephritis, which is usually characterized by immune complex deposition causing a diffuse, proliferative glomerulonephritis. Lupus nephritis and renal vasculitis are the most frequent causes of renal failure in multisystem autoimmunity.